(3TQM GdSQGLjIs - (3YHO GdeMSf GdQheis; (3SQGL GdOjf CHh WGgQ eMeO Hf eMeO Hf YHO GdQTjO GdSLGhfOj GdMfaj,J (B598 (3g` ? s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd Gdehdi GdTjN GdEeGe SQGL GdedI hGdOjf eMeO Hf YHO GdQTjO GdSLGhfOi fhQ Gddg eQbOg s
(3BNQgG (B:s
(3dCf cdGke efgeG dGjQK ef UGMHg eG hQK efg abO ELJeY dCe cd efgeG YTQhf hdHfJg SJhf hddhdGg YTQI Je HYhf Gddg JYGdi ai TgQ QLH HJGQjN SfI (B967(3g` s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdg hbajI HGSe GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi GdHjQhJis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdESdGejs